High altitude ducts causing abnormal wave propagation in coastal area of Korea - Lim, Tae Heung; Wang, Sungsik; Chong, Young Jun; Park, Yong Bae; Ko, Jinwon; Choo, Hosung (Microwave and Optical Technology Letters, 2020)
This article analyzes the number of duct occurrences in the Korean coastal area by seasonal statistical histograms using massive atmospheric data sets collected from 2010 to 2017 at four meteorological observatories. In order to estimate electromagnetic wave propagation characteristics in the presence of the duct atmosphere, we obtain and examine the path loss values by using the advanced refractive prediction system (AREPS) software applying the massive refractive index data set and the actual Korean coastal terrain data. These results are then fitted using Burr Type XII PDF curves to derive quantitative mean and variance values. To verify the suitability of the simulated path losses in the proposed analysis, the measurement of the path losses between Jeung-do and Heuksan-do are carried out in October 2017. The measurements and simulations of the autumn results are fitted by Burr Type XII CDF curves and agree well with each other.
Keywords: Atmospheric data; Coastal terrain; Meteorological observatories; Prediction systems; Propagation interference; Refractive index data; Statistical histograms; Tri-linear models; duct; propagation interference; refractive index; trilinear modeling